A Decade of Water Storage Changes Across the Contiguous United States From GPS and Satellite Gravity. Issue 22 (19th November 2019) - Adusumilli, S.; Borsa, A. A.; Fish, M. A.; McMillan, H. K.; Silverii, F.
Abstract: Increased climate variability is driving changes in water storage across the contiguous United States (CONUS). Observational estimates of these storage changes are important for validation of hydrological models and predicting future water availability. We estimate CONUS terrestrial water storage anomalies (TWSA) from 2007–2017 using Global Positioning System (GPS) displacements, constrained by lower‐resolution TWSA observations from Gravity Recovery and Climate Experiment (GRACE) satellite gravity—a combination that provides higher spatiotemporal resolution than previous estimates. The relative contribution of seasonal, interannual, and subseasonal TWSA varies widely across CONUS watersheds, with implications for regional water security. Separately, we find positive correlation between TWSA and the El Niño/Southern Oscillation in the southeastern Texas‐Gulf and South Atlantic‐Gulf watersheds and an unexpected negative correlation in the southwest. In the western United States, atmospheric rivers (ARs) drive a large fraction of subseasonal TWSA, with the top 5% of ARs contributing 73% of total AR‐related TWSA increases. Plain Language Summary: Policymakers and water resource managers need accurate information about changes in water availability. Water storage is difficult to measure due to the limitations of current models and the challenges of directly observing water in snowpack and aquifers. We circumvent these limitations by combining surface heights from over a thousand Global Positioning System stations with gravity data from orbiting satellites to produce observations of weekly freshwater change across the contiguous United States between 2007 and 2017. Using this novel methodology, we measured changes in freshwater across the continent, both over the course of any given year and between years. We identified several instances where there were large changes in freshwater storage in a short period; in particular, we found that rainfall from only 20 atmospheric river storms, which lasted from hours to days in the western United States, provided over 2.5 times the amount of water from the remaining 391 storms combined. Key Points: A novel combination of GPS and GRACE provides higher‐resolution water storage than GRACE alone, improving water availability analysis The ratio of interannual to seasonal water storage change varies widely across the United States, highlighting local vulnerability to water stress Atmospheric river (AR) events drive rapid water storage increases across the West, with the top 5% of ARs contributing 73% of the AR total